Pengaruh Kompensasi Dan Iklim Kerja Terhadap Semangat Kerja Karyawan Pada PT. Rimba Raya Lestari Di Kecamatan Loa Kulu - Katmi Sari; Erwinsyah Erwinsyah; Sugeng Raharjo (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract:PT. Rimba Raya Lestari is one of the companies engaged in the industry and trade polywood that located in the Yos Sudarso street, Jembayan District Loa Kulu. The problem of compensation where employees feel that during the last two years have never experienced a raise in salary but the ranks of leaders expreinced a salary increase every six months, overtime pay perceived by employees inadequate and not in accordance with overtime hours performed by employees and employee facilities perceived employee has not been able to help employees complete their work within the given deadline.The purpose of this study is to determine, Does Compensation and Work Climate have a simulataneous influence on Spirit At Work At PT. Rimba Raya Lestari In Loa Kulu City, to know, Is The Compensation and Working Climate has Partially influence on Employee Spirit Work At PT. Rimba Raya Lestari In Loa Kulu City.The total population in this study amounted to 1283 people and the sample used amounted to 93 people. Analyzer in this research is T Test and F Test.The results of F test calculation (simultaneous / joint correlation), compensation variable (X1) and work climate (X2) and simultaneously affect pirit At Work, “That, Compensation and Work Climate Variables have a simultaneous influence on Employee Morale At PT. Rimba Raya Lestari In Loa Kulu City” Is accepted and proven to be true.From both result of partial correlation test seen the biggest compensation variable compared to work climate variable, so that compensation variable is the most dominant variable affecting morale. From the description, it can be concluded that the third hypothesis in this study “That, Variable Compensation is the most dominant influence on Job Morrum At PT. Rimba Raya Lestari In Loa Kulu City” is received and proven by the truth. Keywords: Compensation, Working Climate, And Spirit At Work